Role of MRI defecography in assessment of pelvic floor pathologies - Rafiq, Suhail; Posh, Sheema; Shafi, Fahad; Riyaz, Sheikh (International Journal of Advances in Medicine, 2019)
Background: Functional disorders of the pelvic ﬂoor are a common clinical problem. Diagnosis and treatment of these disorders, which frequently manifest with nonspeciﬁc symptoms such as constipation or incontinence, remain difﬁcult. MR Defecography has emerged over the last decade as a modality which additionally images the pelvic floor function in real time besides combining the advantages of previously used modalities and that of magnetic resonance i.e. multiplanar imaging, good temporal resolution and lack of radiation exposure. Dynamic MRI defecography is a relatively new imaging protocol which can be extremely useful in identification of anatomic and functional pelvic floor dysfunction such as organ prolapse, anismus and fecal incontinence. Excellent demonstration of the perirectal soft tissues allows assessment of spastic pelvic ﬂoor syndrome and descending perineum syndrome and visualization of enteroceles. The aim of the study was to assess causes of pelvic floor dysfunction. Methods: Authors evaluated 25 patients with cine Magnetic Resonance Defecography at our center between December 2018 and 15th May 2019. MR Defecography was done with help of 3 Tesla Somatom Seimens MRI. Ultrasound jelly was instilled into the rectum of patient via a short flexible tube while the patient lies in the lateral decubitus position on the scanner table before being moved into the gantry and was asked to defecate when instructed. Scanning was done in four phases-resting, straining, squeezing and defecation as per the standard protocol while patient lied supine. Results: Most common complaint encountered was that of constipation. Patients in age group 20-70 years were studied. Maximum patient were of the age group 40-50 years. Most common finding was organ prolapse in total 9 patients with anterior rectocele in 6 patients followed by rectal prolapse. Conclusions: Magnetic resonance defecography is an excellent modality for assessment of pelvic floor disorders. It has very good temporal resolution and high soft tissue contrast, also allows visualization of the pelvic floor function in real-time without any radiation load. Imaging the defecation process in real-time leads to a definitive diagnosis in cases of dysfunctional defecation and a precise diagnostic and pre-operative assessment in cases of organ prolapse.